THE IMPACT OF DIGITALIZATION ON MSME PERFORMANCE: A QUALITATIVE STUDY ON 3 KG LPG DISTRIBUTION OUTLETS - Mariska Sisilia; Melva Melany Sitompul (PT. Jurnal Center Indonesia Publisher, 2026)
Digitalization has become a key strategy for enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) amidst advances in information technology and changes in consumer behavior. The use of various digital platforms, such as social media, marketplaces, digital payment applications, and technology-based financial recording systems, is expected to improve operational efficiency and expand marketing reach. However, the level of digital technology utilization by 3 Kg LPG distribution outlets remains varied, necessitating a more in-depth study of the impact of digitalization on business performance. This study aims to analyze the impact of digitalization on MSME performance based on interviews with owners and managers of 3 Kg LPG distribution outlets under PT Pinang Baris Langit Biru. The study employed a qualitative approach with descriptive methods. Data were collected through in-depth interviews, observations, and documentation of 3 Kg LPG distribution outlets that have implemented digitalization in their business activities. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research results indicate that the implementation of digitalization has a positive impact on MSME performance, particularly at 3 Kg LPG distribution outlets, including increasing sales, expanding market share, accelerating transaction processes, improving promotional effectiveness, and simplifying business administration and financial management. However, several obstacles remain, such as low digital literacy, limited human resources, and limited access to technology. Therefore, support in the form of training, mentoring, and government policies is needed to improve digital capabilities at 3 Kg LPG distribution outlets so that digital transformation can proceed optimally.